2018
DOI: 10.5194/nhess-18-3327-2018
|View full text |Cite
|
Sign up to set email alerts
|

Rain attenuation prediction model for satellite communications based on the Météo-France ensemble prediction system PEARP

Abstract: Abstract. This paper presents an example of the usage of ensemble weather forecasting for the control of satellite-based communication systems. Satellite communication systems become increasingly sensitive to weather conditions as their operating frequency increases to avoid electromagnetic spectrum congestion and enhance their capacity. In the microwave domain, electromagnetic waves that are conveying information are attenuated between the satellite and Earth terminals in the presence of hydrometeors (mostly … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The validation is a good agreement between measured and predicted attenuation using this model, but has not been compared with other important rain attenuation models high The size of the area is not defined for a specific set of parameters [92] Not validated -…”
Section: Comparative Study Of Slant Link Rain Fade Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…The validation is a good agreement between measured and predicted attenuation using this model, but has not been compared with other important rain attenuation models high The size of the area is not defined for a specific set of parameters [92] Not validated -…”
Section: Comparative Study Of Slant Link Rain Fade Modelsmentioning
confidence: 99%
“…Empirical models SAM model [32] Singapore [33] Garcia [34] GSST [66] LU model [68] Karasawa [88] Breakpoint [29] Unified [89] YLO model [12] Statistical models M-K model [90] MARIMA [91] ITU-R P.618 [45] PEARP [92] Das Model 1 [93] Physical models Bryant [37] Crane TC [94] PM Model [95] SC EXCELL [62] Fade models Japan [96] Das model 2 [97] ITU-R P.1623 [98] Dao model [99] Learning-based AANN [100] The SAM model [32] has evolved through some previously published articles [101].…”
Section: Rain Fade Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…They used a Ka-band with an antenna with a diameter of above 7.2m in tropical regions to prove this. Dahman et al [3] propose a binary decision probabilistic method for Ka frequency rain attenuation forecast using a predetermined threshold. It is a known protocol adjusted for probabilistic weather forecasts in a communication satellite control loop.…”
Section: Related Workmentioning
confidence: 99%
“…Notably good statistical agreements were reported at 20.2 GHz in the south of France for small scale diversity sites over a one-year period [11]. Other studies have shown promises for the applications of NWP forecasts directly to FMTs [12], [13], or similarly for space missions [14], [15]. A more thorough statistical validation of the NWP performances would however still benefit any design based on them.…”
Section: Introductionmentioning
confidence: 96%